TKI-resistant ALK-rearranged lung adenocarcinoma with secondary CTNNB1 p.S45V and tertiary ALK p.I1171N mutations - Ouseph MM (Dove Medical Press, 2019)
Madhu M Ouseph,1 Angela Taber,2 Humera Khurshid,3 Russell Madison,4 Bassam I Aswad,1 Murray B Resnick,1 Evgeny Yakirevich,1 Siraj M Ali,4 Nimesh R Patel11Department of Pathology, Rhode Island Hospital and Alpert Medical School at Brown University, Providence, RI 02903, USA; 2Division of Medical Oncology, Miriam Hospital and Alpert Medical School at Brown University, Providence, RI 02906, USA; 3Division of Medical Oncology, Rhode Island Hospital and Alpert Medical School at Brown University, Providence, RI 02903, USA; 4Foundation Medicine, Inc., Cambridge, MA 02141, USAAbstract: Anaplastic lymphoma kinase (ALK)-rearranged non-small cell lung cancer (NSCLC) is an important molecular subgroup of tumors that are typically sensitive to tyrosine kinase inhibitors (TKIs). Although a substantial portion of patients benefit from TKIs, this approach is complicated by intrinsic and acquired resistance. We report a patient with ALK-rearranged NSCLC who showed an initial response to targeted therapy, but developed resistance to multiple TKIs. Serial comprehensive genomic profiling (CGP) was performed at four independent points during the clinical course. We review the pathology and clonal progression of the tumor, with CGP identifying a secondary CTNNB1 p.S45V mutation after the initiation of targeted therapy, followed by tertiary ALK p.I1171N. The presence of an alteration in a second oncogenic driver gene suggests a possible mechanism for resistance, and a secondary therapeutic target. Due to the involvement of Wnt signaling in the pathogenesis of many tumors and its association with immune evasion, a variety of therapeutic strategies are being developed to target this pathway. This case exemplifies the challenges of targeted therapeutics in the face of tumor progression, as well as the increasing role of genomics in understanding tumor biology.Keywords: cancer, genomics, profiling, beta-catenin, resistance